Peningkatan Pengetahuan dan Keterampilan Ibu dalam Pemantauan Tumbuh Kembang serta Pola Konsumsi Omega 3 pada Anak - Ramadhani, Melati Apriliana; Sofiyanti, Ida; Roni, Abdul (INDONESIAN JOURNAL OF COMMUNITY EMPOWERMENT (IJCE), 2021)
Nutrition is one of the determinants of the quality of human resources. Good nutritional conditions can be achieved when the body gets enough nutrients to be consumed to allow physical growth, brain development, and the ability to achieve optimal levels of health. Nutrients that play a vital role in the development process of brain neuron cells for baby intelligence are fatty acids. The purpose of this community service program is to increase the knowledge and skills of the community, especially mothers in monitoring child growth and development, as well as adding an explanation on the importance of providing fatty acid intake, one of which is omega 3, for toddlers and children. The implementation method in this community service program consists of location surveys, coordination meetings of the distribution team per group, socialization of activities, and monitoring and evaluation of the results of the community knowledge program. The result of this community service is that activities run well and smoothly. The material presented received a good response and enthusiasm from the community. Knowledge of the importance of providing omega 3 and skills in monitoring child development can be well received by the community with the results of the participant posttest, 33.33% excellent results, 50% good categories, and 16.67% adequate. The conclusion of this service activity is that the activity has been carried out well, this can be seen from the community enthusiastically following the activity until the end, and community service activities have an impact on the results ranging from very good to sufficient knowledge of skills in monitoring growth and development and the importance of providing omega 3 in children.Â ABSTRAKGizi merupakan salah satu penentu kualitas sumber daya manusia. Kondisi gizi baik dapat dicapai bila tubuh memperoleh cukup zat gizi yang dikonsumsi sehingga memungkinkan terjadinya pertumbuhan fisik, perkembangan otak, dan kemampuan untuk mencapai tingkat kesehatan optimal. Zat gizi yang berperan vital dalam proses tumbuh kembang sel sel neuron otak untuk kecerdasan bayi adalah asam lemak. Tujuan program pengabdian kepada masyarakat ini adalah untuk meningkatkan pengetahuan dan keterampilan masyarakat, khususnya ibu-ibu dalam pemantauan tumbuh kembang anak, serta ditambah pula adanya pemaparan mengenai pentingnya pemberian asupan asam lemak, salah satunya adalah omega 3, pada balita dan anak. Metode pelaksanaan pada program pengabdian ini terdiri dari survey lokasi, rapat koordinasi tim pembagian per kelompok, sosialisasi kegiatan, serta adanya monitoring dan evaluasi hasil program pengetahuan masyarakat. Hasil dari pengabdian masyarakat ini adalah kegiatan berjalan dengan baik dan lancar. Materi yang disampaikan mendapatkan respon dan antusias yang baik dari masyarakat. Pengetahuan tentang pentingnya pemberian omega 3 serta keterampilan dalam pemantauan tumbuh kembang anak dapat diterima dengan baik oleh masyarakat dengan adanya hasil posttest peserta, hasil sangat baik sebanyak 33,33%, katagori baik sebanyak 50%, dan cukup sebanyak 16,67%. Kesimpulan dari kegiatan pengabdian ini adalah kegiatan telah terlaksana dengan baik, hal ini dapat terlihat dari masyarakat secara antusias mengikuti kegiatan hingga akhir, dan kegiatan pengabdian masyarakat memberikan dampak hasil dengan rentang sangat baik sampai cukup pada pengetahuan keterampilan dalam pemantauan tumbuh kembang dan pentingnya pemberian omega 3 pada anak.